2016
DOI: 10.3390/en9070534
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Transient Behaviour of a Variable Speed Pump-Turbine during a Pumping Power Reduction Scenario

Abstract: To achieve the carbon free electricity generation target for 2050, the penetration of renewable energy sources should further increase. To address the impacts of their unpredictable and intermittent characteristics on the future electricity grid, Pumped Hydro Energy Storage (PHES) plants should enhance their regulation capability by extending their continuous operating range far beyond the optimal normal working range. However, for the time being, the regulation capability of the new generation of PHES, equipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…9). When the instabilities start up, forcing frequencies are highlighted and they partly coincide with those identified in the pumping power reduction scenario obtained by speed reduction (St=0.33, St=0.66) [16], but the most remarkable ones are related to the rotating stall phenomenon highlighted during the rapid closure of the wicket gates.…”
Section: Analysis Of Transient Flow In Pump Turbine During Wicket Gatmentioning
confidence: 99%
See 1 more Smart Citation
“…9). When the instabilities start up, forcing frequencies are highlighted and they partly coincide with those identified in the pumping power reduction scenario obtained by speed reduction (St=0.33, St=0.66) [16], but the most remarkable ones are related to the rotating stall phenomenon highlighted during the rapid closure of the wicket gates.…”
Section: Analysis Of Transient Flow In Pump Turbine During Wicket Gatmentioning
confidence: 99%
“…Since the study was aimed at reproducing the load rejection scenario of a pump-turbine, a large adjustable guide vane opening of 23.4 deg, presenting an unstable behavior in pumping mode [16], was considered as starting configuration. Fig.…”
Section: Pump-turbine Modelmentioning
confidence: 99%
“…During the dynamic process of extreme condition (i.e. load rejection or pump outage) with the non optimal closing law, the rise of the unit rotational speed and the water hammer pressure will exceed the maximum design value, which cause the runaway speed of the PSHU, abnormal vibration or active guide vane asynchronous and other negative phenomena [8,9]. OGVCS plays an important role in ensuring the security and stability of the power grid, and several methods have been proposed to deal with the OGVCS problem.…”
Section: Of 26mentioning
confidence: 99%
“…At present, the pump-turbine modeling based on the characteristic curves has been widely used. In this paper, pump-turbine is be described as the torque function and flow function of guide vane opening, generator rotational speed and water head, shown as formula (8) [32]. The analytic expression of nonlinear functions of ( ) m f ⋅ and ( ) q f ⋅ are difficult to obtain.…”
Section: Model Of Pshumentioning
confidence: 99%
“…It has been reported that the intermittency and the variability of renewable energy resources can adversely affect flexibility [3]. To address this problem, the role of pumped hydroelectric storage (PHES) has received attention as a flexible resource; it has a fast start-up and ramping characteristics [4][5][6][7]. In Korea, the PHES start-up is 4 min, while those for a hot-start combined cycle gas turbine and hot-start coal steam turbine are 57 and 197 min, respectively.…”
Section: Introductionmentioning
confidence: 99%